2020
DOI: 10.3847/2041-8213/ab775b
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino Process in Core-collapse Supernovae with Neutrino Self-interaction and MSW Effects

Abstract: We calculate the abundances of 7Li, 11B, 92Nb, 98Tc, 138La, and 180Ta produced by neutrino (ν)-induced reactions in a core-collapse supernova explosion. We consider the modification by ν self-interaction (ν-SI) near the neutrinosphere and the Mikheyev–Smirnov–Wolfenstein (MSW) effect in the outer layers based on time-dependent neutrino energy spectra. Abundances of 7Li and the heavy isotopes 92Nb, 98Tc, and 138La are reduced by a factor of 1.5–2.0 by the ν-SI. In contrast, 11B is relatively insensitive to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In addition, some rare nuclei such as 7 Li, 11 B, 138 La and 180 Ta are produced by neutrino reactions in SN nucleosynthesis [26]. Yields of light rare nuclei 7 Li and 11 B [27] as well as heavy nuclei including short-lived nuclei [28] depend on the neutrino mass hierarchy. Those nuclear yields are then also a probe of the flavor conversions induced by atomic electrons in stars.…”
Section: The Fraction Of Conversion Per Passing Is Fmentioning
confidence: 99%
“…In addition, some rare nuclei such as 7 Li, 11 B, 138 La and 180 Ta are produced by neutrino reactions in SN nucleosynthesis [26]. Yields of light rare nuclei 7 Li and 11 B [27] as well as heavy nuclei including short-lived nuclei [28] depend on the neutrino mass hierarchy. Those nuclear yields are then also a probe of the flavor conversions induced by atomic electrons in stars.…”
Section: The Fraction Of Conversion Per Passing Is Fmentioning
confidence: 99%
“…Extensive calculations showed that another short-lived radioactive isotope 92 Nb and stable ones 138 La and 180 Ta also are produced in the ν-process. These nuclei are useful to constrain still unknown mass hierarchy [286][287][288]. Figure 7 shows an example of the 7 Be and 92 Nb abundances as a function of the Lagrangian mass M r .…”
Section: Nuclear Electroweak Response and ν-Astrophysicsmentioning
confidence: 99%
“…Therefore, a substantial region of the preferred mass range by IceCube is disallowed by the CMB bound (see fig. (10)).…”
Section: Inverted Hierarchymentioning
confidence: 99%
“…Self interaction in between the neutrinos has been an active topic of interest in different sectors of cosmology [1][2][3][4][5][6][7][8], astro-physics [9,10] and laboratory based neutrino experiments [11][12][13]. In the recent years it has been studied extensively in the context of resolving H 0 tension [3,4].…”
Section: Introductionmentioning
confidence: 99%